Chatbots from the users’ perspective: A systematic literature review - Harmat, Vanda (Vezetéstudomány / Budapest Management Review, 2024)
The application of chatbots in business organizations is becoming ever more widespread. When developing an interface, besides the aspects of efficiency, human values, and users’ social and emotional needs also should be respected. From this perspective, understanding the impact of human-chatbot interaction (HCI) on individuals’ behavior is paramount. This article aims to contribute to the exploration of users’ perspectives on chatbots through a systematic literature review of 31 papers examined with content analysis. The results show that besides functionality, entertainment is also important for users during HCI. The growing magnitude of humanlike attributes that could support this need does however not provide users with the feeling of satisfaction but can evoke feelings of anxiety instead.